Climate policy uncertainty and power generation investments: A real options-CVaR portfolio optimization approach - ShahNazari, M.; Maybee, Bryan; Whale, J.; McHugh, A. (Elsevier Ltd, 2015)
A decision support framework has been provided to assist investors with long-term decision-making for investment choices in power generation assets under uncertain climate policy. The model combines real options analysis and modern portfolio optimization theory. A long-term correlation between carbon and renewable portfolio standard certificate prices is used to model the interaction of climate policies, with a case study being developed to investigate the optimal choice of capacity additions to an existing mix of power generation assets in Australia. The findings show that there is potential for investors to fully hedge their existing fossil fuel based generation assets through the addition of on-shore wind capacity. The model developed allows for (1) the investigation of investment risk and return under uncertain climate policies, and (2) the study of interaction among green policies.